Physiologic specialization of Puccillia graminis tritiei on wheat (Triticum aestivum) in India during 2002-2004 - BHARDWAJ, S C; PRASHAR, M; SINGH, S B (The Indian Journal of Agricultural Sciences, 2011)
Nine pathotypes of Puccinia graminis Pers. f sp tritici Erikiss & Henn. were observed in 187 samples ofblack rust of wheat analysed during 2002-04 from different parts of India. Pathotype 62G29 virulent on Sr2, Sr5, Sr6, Sr7b, 8r8, Sr9b, Srge, Sr11, Sr12 and Sr28 was the most common. Frequency of pathotype 62G29-1 which is restricted to Tamil Nadu and is virulent on Sr24 has reduced considerably. Virulence on 8r25, 8r26, 8r27, 8r31,8r32, Sr35,Sr37,Sr39 , Sr40 andSr43 was not recorded. Change in virulence pattern was not observed.